Start-ups and SMEs concepts, methodologies, tools, and applications (Business Science Reference, an imprint of IGI Global, 2020)
"This book examines the strategies and concepts that will assist small and medium-sized enterprises to achieve competitiveness. It also explores the latest advances and developments for creating a system of shared values and beliefs in small business environments"--